Evaluation of Performance Employee (Study on Faculty of Educational Science Manado State University-Indonesia ) - Tuerah, Roos M.S (International Journal of Scientific Research and Management (IJSRM), 2018)
The main problem in this study related to Human Resources (HR) which is one of the main factors in improving the productivity of performance in the organization or agency. Therefore, it is necessary to have competent human resources that can support the improvement of performance achievement. The study aims to determine the performance of administrative staff at the science faculty of the Manado State University, Indonesia. By using a qualitative approach, respondents are taking data of all employees in the faculty of education, which amounted to 35 people. The conclusion shows that the performance of Employees in the faculty of education, Manado State University is influenced by the factors: Effectiveness and efficiency, Authority (authority), discipline, initiative. Performance appraisal of employees follows the applicable government regulations. It takes a sense of responsibility from all employees in carrying out their duties.